Effect, safety, timing and dose of thoracic radiotherapy plus third-generation EGFR-TKIs as first-line treatment in patients with EGFR-mutated oligo-organ metastatic NSCLC - Gu, Xinhang; Geng, Jiaxiao; Sun, Hongfu; Cao, Qiang; Yi, Yan; Li, Baosheng (Frontiers in Oncology, 2025)
BackgroundEpidermal growth factor receptor (EGFR) tyrosine kinase inhibitor (TKI)-based combination therapy modalities for patients with EGFR-mutated stage IV non-small cell lung cancer (NSCLC) are being investigated. We evaluated the value and safety of third-generation EGFR-TKIs combined with thoracic radiotherapy (TRT) in patients with oligo-organ metastatic, along with the optimal TRT timing and dose.MethodsWe retrospectively enrolled patients with EGFR-mutated oligo-organ metastatic NSCLC who received first-line third-generation EGFR-TKIs from 2018 to 2023. Patients were divided into TKI-alone and TKI+TRT groups according to whether TRT was added. Propensity score matching (PSM) was implemented to decrease bias. The primary endpoint was progression-free survival (PFS). Secondary endpoints included overall survival (OS) and safety.ResultsA total of 236 patients were included, the median follow-up was 28.4 months. After PSM, baseline characteristics were balanced between the TKI+TRT (n=69) and TKI-alone (n=108) groups. Compared with the TKI-alone group, the TKI+TRT group presented significantly better PFS (28.6 vs. 19.8 months, hazard ratio [HR]=0.48, P = 0.00024) and OS (42.2 vs. 35.1 months, HR = 0.54, P = 0.039). In patients who received TRT, the tumor shrinkage group demonstrated significantly improved PFS (HR = 0.36, P = 0.0035) and OS (HR = 0.13, P = 0.0012) compared to the tumor enlargement/Stabilization group. The high-dose group showed superior PFS (HR = 0.43, P = 0.011) and OS (HR = 0.36, P = 0.023) compared to the low-dose group. Only 5.8% of patients in the TKI+TRT group developed grade ≥3 pneumonitis.ConclusionIncorporating TRT provided significant survival benefits in patients with oligo-organ metastatic NSCLC who received first-line third-generation EGFR TKIs, with acceptable side effects. The administration of higher radiation doses during a phase of tumor shrinkage may be associated with optimal outcomes.